MAKNA FILOSOFIS PADA PERUPAAN KEPALA WAYANG CEPAK INDRAMAYU TOKOH PANJI SONGSONG - Rofiqoh Djawas (Universitas Trisakti, 2016)
AbstractIndramayu has a diversity of artistic traditions and one of them is Wayang Golek Cepak (rod puppet theatre). Currently, the puppet show is on the verge of extinction due to the lack of support of the community and local government. Meanwhile, if it is traced as the locality, Wayang Golek Cepak is one of the oldest art relics in Indramayu. The evidence has shown the fact about the presence of a puppet artifact which is over300 years old that belongs to a puppeteer, Akhmadi.Wayang Cepak of Indramayu has 7 characters of knight that are called as Panji. They are believed historically as the local hero characters of Indonesia. One of the characters who are considered as sacred by the puppeteers is Panji Songsong. This study focused on the phylosophy meaning and aesthetic value of the last Panji Songsong's form. It was ristricted to the study of the artifact of Panji Songsong's head that still remainsdue to the disappearance of its original identity of its fashion. This study was conducted by using the Concept of East Cultural Aesthetics which included Jakob Sumardjo's Esa Theory and Three Pattern Theory. The analysis from the study concluded that Panji Songsong has sacred meaning of divinity values. In its relation to the concept of aesthetic culture of the East, PanjiSongsong is considered as containing the mystical contents. According to the Three Pattern Theory, each piece of art that has a mystical meaning comes out as the result of the fusion of paradoxical dualism that has been unified in the indistinguishable form. Thus, such condition is thought as the cause of the sacred meaning that Panji Songsong possesses and why the character is frequently used as the intermediary toinvite the ancestral spirits. AbstrakIndramayu memiliki keragaman seni tradisi, salah satunya adalah kesenian Wayang Golek Cepak. Saat ini, kesenian tersebut diambang punah, karena minimnya dukungan masyarakat dan pemerintah setempat. Sementara jikadirunut secara lokalitas, Wayang Cepak merupakan salah satu peninggalan kesenian tertua yang ada di Indramayu. Terbukti dengan adanya artefak wayang milik dalang Akhmadi yang berusia 300 tahun lebih. Wayang Cepak Indramayu, memiliki 7 tokoh ksatria yang diperankan oleh tokoh Panji. Pada sejarahnya Panji diyakini sebagai pahlawan yang memilikikarakter lokal Indonesia. Salah satu tokoh Panji yang paling disakralkan oleh para dalang adalah Panji Songsong. Penelitian ini menitikberatkan pada makna filosofis dan nilai estetis perupaan Panji Songsong, dengan batasan hanya mengkaji kepala artefak Panji Songsong yang masih utuh, karenaidentitas busana sudah hilang keasliannya. Penelitian ini dikaji menggunakan Konsep Estetika Budaya Timur yang di dalamnya mencakup Teori Esa dan Teori Pola Tiga Jakob Sumardjo.Bedasarkan analisa, penelitian ini dapat disimpulkan bahwa Panji Songsong memiliki makna sakral yang di dalamnya terdapat nilai-nilai ketuhanan. Berkaitan dengan Konsep Estetika Budaya Timur, Panji Songsong dianggap membawa hal yang mistis. Pada Teori Esa dan Pola Tiga, setiap benda seniyang memiliki makna mistis tersebut hadir dari peleburan paradoks dualisme, menjadi satu kesatuan bentuk tanpa pembeda pada perupaannya. Hal tersebut yang menjadikan tokoh Panji Songsong memiliki makna sakraldan kerap dijadikan sebagai perantara untuk mendatangkan roh-roh leluhur